Nickel-nickel molybdenum gradient lamellar structure alloy and preparation method thereof
The formation of nickel/nickel-molybdenum gradient layered alloy is solved by electrochemical deposition, which solves the problem of insufficient protection of traditional nickel-based alloy coatings under high load bearing conditions, and achieves higher wear resistance and stability. It is suitable for guns Inside the pipe, harsh environments such as the inner chamber.
Patent Information
- Application Number
- CN202411399516.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2024-12-31
AI Technical Summary
Traditional homogeneous structure nickel-based alloy coatings are difficult to meet the surface protection requirements under high load conditions. A single grain size gradient structure or laminate structure is prone to failure under high temperature and high speed impact conditions, and it is difficult to meet the harshness of the barrel inner chamber. Environmental requirements.
By electrochemical deposition, the pure nickel layer and nickel-molybdenum alloy layer are alternately deposited, and the grain size gradient is controlled, and the micro-coarse crystal-ultrafine crystal-nano crystal-transition is realized from the inside out, and the ultra-fine nanocrystal structure is combined to form nickel. /Nickel-molybdenum gradient laminate structure alloy.
It improves the plastic deformation capability and stability of nickel-based alloys, extends the service life of the structure, broadens the application range under high temperature, heavy load, high-speed mechanical impact and other conditions, and significantly reduces the wear rate.
Smart Images

Figure CN119221058A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of metal materials, and in particular relates to a nickel-nickel-molybdenum gradient layer structure alloy and a preparation method thereof. Background Art
[0002] Nickel-based alloys are widely used in advanced manufacturing, energy, electronics, aerospace and other fields due to their high strength, high wear resistance, good corrosion resistance and other performance advantages. They are important coating materials for surface protection of key components of high-end equipment. For example, in the inner bore of a gun barrel, nickel-based alloy plating can be used as a substitute for traditional hard chrome plating, which can avoid serious pollution caused by electroplating hard chrome and is beneficial to environmental protection and green sustainable development.
[0003] Compared with other nickel-based alloy coating preparation processes, the electrodeposition method has distinct advantages such as low cost, good coating uniformity, almost unlimited sample combination size and high controllability, and is widely used in the fields of surface wear resistance and corrosion protection. However, due to the increasingly harsh service environment of the material surface, the traditional homogeneous structural coating can no longer meet the corresponding surface protection needs. For example, the traditional homogeneous coarse-grained nickel-based alloy has poor strength and low surface hardness, and it is difficult to meet the wear protection under high-load conditions. At the same time, the homogeneous nanocrystalline nickel-based alloy is brittle and easy to crack, and it is difficult to achieve effective protection under harsh conditions. At present, in response to the demand for new metal coating materials, gradient structures and lamellar structures have been widely introduced into their design and development, in order to achieve a significant improvement in their surface protection performance. Patent documents CN104862748A, CN202010070014.6, CN115449867A, and CN202311064252.6 respectively disclose a grain-scale gradient metal nickel and a controllable preparation method thereof, a gradient structure nickel-tungsten alloy, a preparation method and a new layered structure, a preparation process of an electrodeposited single-phase composition gradient nanocrystalline iron-cobalt-nickel alloy, and a highly wear-resistant and corrosion-resistant layered heterogeneous nickel-based alloy and a preparation method thereof. A single grain-size gradient structure is very susceptible to nanocrystal coarsening under high load or high temperature, resulting in rapid failure of the overall gradient structure and sharp degradation of performance; at the same time, the mechanical properties of adjacent lamellae in the lamellar structure are significantly different, and stress concentration and strain localization are easily generated at the interface, which eventually leads to lamella peeling failure. This makes it difficult for a single grain-size gradient structure or a lamellar structure to meet the service requirements under extreme working conditions (such as high temperature, high-speed impact, oxidation and other multi-field coupling conditions on the inner surface of the gun barrel). Summary of the invention
[0004] The object of the present invention is to provide a nickel / nickel-molybdenum gradient lamellar structure alloy and a preparation method thereof.
[0005] The technical solution to achieve the purpose of the present invention is: a method for preparing a nickel-nickel-molybdenum gradient layer structure alloy, which adopts electrochemical deposition, uses nickel as a consumable anode, and alternately deposits pure nickel layers and nickel-molybdenum alloy layers under the action of direct current; wherein by controlling the composition of the plating solution, the current density and the plating solution temperature, the pure nickel layer from the inside to the outside has a grain size gradient of micron coarse crystal-ultrafine crystal-nanocrystalline transition, and the nickel-molybdenum alloy layer is an ultrafine nanocrystalline structure.
[0006] Furthermore, the method specifically comprises the following steps:
[0007] Step (1): Substrate pretreatment: surface grinding, polishing and degreasing are performed in sequence, followed by water washing, acid washing activation and water washing;
[0008] Step (2): immersing the treated substrate in a pure nickel electroplating solution, and preparing a pure nickel layer by direct current electrodeposition;
[0009] Step (3): taking out the sample obtained in step (2), washing it with water, acid washing it to activate the pure nickel layer, washing it with water, and then immersing it in a nickel-molybdenum alloy electroplating solution to prepare a nickel-molybdenum alloy coating by direct current electrodeposition;
[0010] Step (4): Take out the sample obtained in step (3), wash it with water, pickle it to activate the nickel-molybdenum alloy layer, and wash it with water, then periodically repeat steps (2) and (3) alternately, and when repeating step (2), adjust the plating solution temperature and current density in real time to achieve the construction of the grain size gradient structure, and finally prepare a nickel / nickel-molybdenum gradient layer structure alloy with M layers of pure nickel layer and M layers of nickel-molybdenum alloy layer respectively and a total number of 2M layers, where M is a positive integer.
[0011] Furthermore, the cathode of the electrochemical deposition is titanium, copper, copper alloy, steel or nickel and nickel alloy.
[0012] Furthermore, the pure nickel electroplating solution in step (2) comprises nickel sulfate hexahydrate at a concentration of 100-300 g / L, nickel chloride hexahydrate at a concentration of 30-45 g / L, boric acid at a concentration of 20-40 g / L, and sodium dodecyl sulfate at a concentration of 0.1-0.5 g / L; and the pH of the pure nickel electroplating solution is adjusted to 4.5±0.5.
[0013] Furthermore, the nickel-molybdenum alloy electroplating solution in step (3) includes nickel sulfate hexahydrate at a concentration of 60-80 g / L, sodium citrate dihydrate at a concentration of 80-100 g / L, sodium molybdate dihydrate at a concentration of 1-3 g / L, vinyl acetate at a concentration of 0.1-0.5 g / L, sodium saccharin at a concentration of 0-5 g / L, and sodium dodecyl sulfate at a concentration of 0.1-0.5 g / L; the pH of the nickel-molybdenum alloy electroplating solution is adjusted to 9±0.5.
[0014] Further, "making the pure nickel layer from the inside to the outside have a grain size gradient of micron coarse grains - ultrafine grains - nanocrystals by controlling the bath composition, current density, and bath temperature" specifically means:
[0015] The deposition current density of the pure nickel layer gradually increases from 40 ± 1 mA / cm² to 80 ± 2 mA / cm² as the number of layers increases. Specifically: 2 When depositing the first layer of the pure nickel layer, the current density is 40 ± 1 mA / cm²; 2 , specifically:
[0016] When depositing the first layer of the pure nickel layer, the current density is 40 ± 1 mA / cm²; 2 ;
[0017] When depositing the Mth layer of the pure nickel layer, the current density is 80 ± 2 mA / cm²; 2 ;
[0018] When depositing the Nth layer of the pure nickel layer, where 1 ≤ N < M and N is a positive integer, the current density is
[0019] The deposition temperature of the pure nickel layer gradually decreases from 75 ± 2 °C to 45 ± 1 °C as the number of layers increases. Specifically:
[0020] When depositing the first layer of the pure nickel layer, the bath temperature is 75 ± 2 °C;
[0021] When depositing the final layer, i.e., the Mth layer of the pure nickel layer, the bath temperature is 45 ± 1 °C;
[0022] When depositing the Nth layer of the pure nickel layer, where 1 ≤ N ≤ M and N is a positive integer, the temperature is
[0023] Further, when depositing the nickel - molybdenum alloy layer, the deposition current density of the nickel - molybdenum alloy layer remains constant as the number of layers increases, being 30 ± 1 mA / cm²; 2 ;
[0024] The temperature of the nickel - molybdenum alloy electroplating bath remains constant as the number of layers increases, being 35 ± 1 °C.
[0025] Further, nickel - tungsten, nickel - cobalt, nickel - iron, nickel - phosphorus, or nickel - boron is used instead of nickel - molybdenum.
[0026] A nickel - nickel molybdenum gradient laminated structure alloy is prepared by the above - mentioned method; the grain size of the pure nickel layer of the nickel - nickel molybdenum gradient laminated structure alloy gradually refines from 2 - 5 μm to 20 - 30 nm; the grain size of the nickel - molybdenum alloy layer is 10 ± 2 nm; the thickness ratio between the pure nickel layer and the nickel - molybdenum alloy layer is 5:1 to 50:1.
[0027] Use of a nickel - nickel molybdenum gradient laminated structure alloy as described above for the inner bore of a gun barrel.
[0028] Compared with the prior art, the present invention has the following significant advantages:
[0029] The present invention provides a nickel / nickel-molybdenum gradient lamellar structure alloy, a preparation method and a novel gradient lamellar structure. By using electrochemical deposition technology and adopting a periodic alternating electrodeposition method, the current density of the pure nickel layer and the plating solution temperature are continuously adjusted, and the deposition parameters of the nickel-molybdenum alloy layer are maintained, a pure nickel layer having a micron coarse crystal-ultrafine crystal-nanocrystalline transition grain size gradient and a nickel-molybdenum alloy layer having an ultrafine nanocrystalline structure can be prepared.
[0030] First, the preparation process of the electrodeposition method is simple, highly controllable, and universal. It only needs to simply adjust the composition of the plating solution to expand from the nickel / nickel-molybdenum alloy system to nickel / nickel-tungsten, nickel / nickel-cobalt, nickel / nickel-iron, nickel / nickel-phosphorus, nickel / nickel-boron, and other nickel-based alloy material systems with a wide range of applications in the fields of aerospace, weapons, and energy. At the same time, adjusting the electrodeposition time and current density can achieve precise control of the layer thickness ratio between the pure nickel layer and the nickel-molybdenum alloy layer in a wide range of 5:1 to 50:1.
[0031] Secondly, the gradient lamellar structure can synergistically exert the coupling effect of the grain size gradient structure and the lamellar structure. On the one hand, the grain size gradient structure of the pure nickel layer can eliminate the difference in mechanical properties at the interface in the lamellar structure, improve the plastic deformation capacity of the overall structure, and avoid interface cracking and peeling failure of the overall coating under high load conditions. On the other hand, the ultrafine nanocrystalline structure nickel-molybdenum alloy layer has high strength, high hardness and high thermal stability, and uses interface constraints to improve the stability of the grain size gradient structure, ensuring that the overall structure has good stability.
[0032] Therefore, the nickel / nickel-molybdenum gradient lamellar structure alloy prepared by the above method can further broaden the application range of nickel-based alloys under harsh service conditions such as high temperature, heavy load, and high-speed mechanical impact, and provide technical reserves for future engineering applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 These are structural characterization diagrams of the electrochemically deposited nickel-nickel-molybdenum gradient lamellar structure alloy sample I of Example 1, wherein (a) is a scanning electron microscope image of the cross-sectional microstructure, (b) is an electron backscatter diffraction image of the cross-sectional microstructure, (c) is the grain size distribution of the pure nickel layer cross-section, and (d) is the cross-sectional hardness value distribution.
[0034] Figure 2These are structural characterization diagrams of the electrochemically deposited nickel-nickel-molybdenum gradient lamellar structure alloy sample II of Example 2, wherein (a) is a scanning electron microscope diagram of the cross-sectional microstructure, (b) is a backscattered electron imaging diagram of the cross-sectional microstructure, (c) is an electron backscattered diffraction diagram of the cross-sectional microstructure of the pure nickel layer, (d) is an electron backscattered diffraction diagram of the cross-sectional microstructure of the pure nickel layer, (e) is a transmission electron microscope diagram of the cross-sectional microstructure of the pure nickel layer, (f) is the grain size distribution of the cross-sectional pure nickel layer, and (g) is the cross-sectional hardness value distribution.
[0035] Figure 3 This is a comparison chart of the wear rates of electrochemically deposited nickel-nickel-molybdenum gradient lamellar structure alloy samples I and II and coarse-grained nickel. DETAILED DESCRIPTION
[0036] To make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be described clearly and completely below. The features and performance of the present invention will be further described in detail below in conjunction with the embodiments.
[0037] Example 1
[0038] This embodiment provides a method for preparing a nickel / nickel-molybdenum gradient layer structure alloy. The total number of layers is 10, and the number of layers of the pure nickel layer and the nickel-molybdenum alloy layer is 5. The thickness of the pure nickel layer gradually decreases from 25μm to 5μm; the thickness of the nickel-molybdenum layer is 1μm. It includes the following steps:
[0039] (1) In this embodiment, a metal nickel plate with a purity of 99.6% is used as a consumable anode, and a metal copper plate is used as a cathode.
[0040] Prepare 1000 ml of pure nickel electroplating solution and nickel-molybdenum alloy electroplating solution respectively, wherein the pure nickel electroplating solution includes chemical reagents of the following concentrations: nickel sulfate hexahydrate: 300 g / L, nickel chloride hexahydrate: 45 g / L, boric acid: 40 g / L, sodium dodecyl sulfate: 0.2 g / L. Weigh the above chemical reagents with a balance, dissolve them with deionized water in a 1000 ml beaker, stir the solution with a magnetic stirrer until it is clear, adjust the pH value of the solution to 4.5±0.5 with a dilute sulfuric acid solution or a dilute ammonia solution, and control the initial temperature of the plating solution to 50±1°C with a heating device;
[0041] The nickel-molybdenum alloy electroplating solution includes chemical reagents of the following concentrations: nickel sulfate hexahydrate: 60 g / L, sodium citrate dihydrate: 80 g / L, sodium molybdate dihydrate: 1.5 g / L, vinyl acetate: 0.2 g / L, saccharin: 2 g / L, sodium dodecyl sulfate: 0.2 g / L. The above chemical reagents are weighed with a balance, dissolved with deionized water in a 1000 ml beaker, stirred with a magnetic stirrer until the solution is clear, adjusted to a pH value of 9±0.5 with a dilute sulfuric acid solution or a dilute ammonia solution, and controlled to an initial temperature of the plating solution at 35±1°C with a heating device.
[0042] (2) The nickel-based sheet structure is prepared by an alternating deposition method, and the specific steps are as follows:
[0043] a. Substrate pretreatment, surface grinding, polishing and degreasing in sequence; then water washing, acid washing activation, and water washing again;
[0044] b. The substrate is immersed in a pure nickel electroplating solution, and a pure nickel layer is prepared by direct current electrodeposition;
[0045] c. The sample was taken out and washed, acid-washed to activate the pure nickel layer, washed, and then immersed in a nickel-molybdenum alloy electroplating solution to prepare a nickel-molybdenum alloy coating by direct current electrodeposition;
[0046] d. The semi-finished product obtained in the above steps is washed with water, pickled to activate the nickel-molybdenum alloy layer, and then washed with water again, and then the direct current deposition of steps b and c is repeated in sequence. At the same time, the current density, plating solution temperature and deposition time in step b are regulated so that the grain size of the pure nickel layer presents a gradient distribution with the number of layers, and a grain size gradient structure is obtained, and finally a nickel / nickel-molybdenum gradient lamellar structure alloy with a total number of 10 layers is prepared.
[0047] (3) Use computer to control current density and deposition time:
[0048] Pure nickel layer deposition current density: During the entire electrochemical deposition process, the current density remains constant at 40mA / cm 2 .
[0049] At the same time, the deposition time of the pure nickel layer is controlled: the deposition time of the first layer is 25 minutes, the deposition time of the second layer is 20 minutes, the deposition time of the third layer is 15 minutes, the deposition time of the fourth layer is 10 minutes, and the deposition time of the fifth layer is 5 minutes.
[0050] NiMo layer deposition current density: During the entire electrochemical deposition process, the current density remained constant at 30mA / cm 2 .
[0051] At the same time, the deposition time of the nickel-molybdenum layer is controlled: the deposition time of each layer is 10 minutes.
[0052] The nickel / nickel-molybdenum gradient lamellar structure alloy sample I was prepared in this embodiment. Figure 1 As shown in (a), the coating quality of sample I is good, the interface is well bonded, and there are no obvious microcracks.
[0053] The grain size distribution of the pure nickel layer in the nickel / nickel-molybdenum gradient lamellar structure alloy sample I is shown in Figure 2. Figure 1 As shown in (b) and (c), the grain size in the direction of the long axis of the grain shows a trend of first increasing and then decreasing, and the specific change is 2430nm→3490nm→3950nm→2630nm→1550nm; the grain size in the direction of the short axis of the grain shows a trend of first decreasing and then increasing, and the specific change is 1760nm→950nm→930nm→820
[0054] nm→1550nm.
[0055] The cross-sectional hardness distribution of Ni / NiMo gradient lamellar structure alloy specimen I is shown in Figure 2. Figure 1 As shown in (d), the hardness of the pure nickel layer gradually increases from 338HV to 425HV, and the specific changes are 338HV→348HV→365HV→394HV→425HV; the hardness of the nickel-molybdenum alloy layer is maintained at 638HV. Figure 3 As shown in the figure, the wear rates under loads of 10N, 20N, 40N, 60N, and 80N are 3.31×10 -6 mm 3 / N·m, 1.19×10 -5 mm 3 / N·m, 1.22×10 -5 mm 3 / N·m, 2.33×10 -5 mm 3 / N·m, 2.07× -5 mm 3 / N·m, compared with coarse-grained nickel (grain size is about 30μm), its wear rate is reduced by 30%, 15%, 46%, 47% and 69% under loads of 10N, 20N, 40N, 60N and 80N, respectively.
[0056] Example 2
[0057] This embodiment provides a method for preparing a nickel / nickel-molybdenum gradient layer structure alloy. The total number of layers is 10, and the number of layers of the pure nickel layer and the nickel-molybdenum alloy layer is 5. The thickness of the pure nickel layer is 15±2μm; the thickness of the nickel-molybdenum layer is 1μm. The method comprises the following steps:
[0058] (1) In this embodiment, a metal nickel plate with a purity of 99.6% is used as a consumable anode, and a metal copper plate is used as a cathode.
[0059] Prepare 1000 ml of pure nickel electroplating solution and nickel-molybdenum alloy electroplating solution respectively. The pure nickel electroplating solution includes chemical reagents of the following concentrations: hydrated nickel sulfate: 300 g / L, hexahydrated nickel chloride: 45 g / L, boric acid: 40 g / L, sodium saccharin: 2 g / L, sodium dodecyl sulfate: 0.2 g / L. Weigh the above chemical reagents with a balance, dissolve them with deionized water in a 1000 ml beaker, stir the solution with a magnetic stirrer until it is clear, adjust the pH value of the solution to 4.5±0.5 with a dilute sulfuric acid solution or a dilute ammonia solution, and control the initial temperature of the plating solution to 75±1°C with a heating device;
[0060] The nickel-molybdenum alloy electroplating solution includes chemical reagents of the following concentrations: nickel sulfate hexahydrate: 60 g / L, sodium citrate dihydrate: 80 g / L, sodium molybdate dihydrate: 1.5 g / L, vinyl acetate: 0.2 g / L, saccharin: 2 g / L, sodium dodecyl sulfate: 0.2 g / L. The above chemical reagents are weighed with a balance, dissolved with deionized water in a 1000 ml beaker, stirred with a magnetic stirrer until the solution is clear, adjusted to a pH value of 9±0.5 with a dilute sulfuric acid solution or a dilute ammonia solution, and controlled to an initial temperature of the plating solution at 35±1°C with a heating device.
[0061] (2) The nickel / nickel-molybdenum gradient layer structure alloy is prepared by an alternating deposition method, and the specific steps are as follows:
[0062] a. Substrate pretreatment, surface grinding, polishing and degreasing in sequence; then water washing, acid washing activation, and water washing again;
[0063] b. The substrate is immersed in a pure nickel electroplating solution, and a pure nickel layer is prepared by direct current electrodeposition;
[0064] c. The sample was taken out and washed, acid-washed to activate the pure nickel layer, washed, and then immersed in a nickel-molybdenum alloy electroplating solution to prepare a nickel-molybdenum alloy coating by direct current electrodeposition;
[0065] d. The semi-finished product obtained in the above steps is washed with water, pickled to activate the nickel-molybdenum alloy layer, and then washed with water again, and then the direct current deposition of steps b and c is repeated in sequence. At the same time, the current density, plating solution temperature and deposition time in step b are regulated so that the grain size of the pure nickel layer presents a gradient distribution with the number of layers, and a grain size gradient structure is obtained, and finally a nickel / nickel-molybdenum gradient lamellar structure alloy with a total number of 10 layers is prepared.
[0066] (3) Use computer to control current density and deposition time:
[0067] Pure nickel layer deposition current density and deposition time: During the entire electrochemical deposition process, the current density is 40-80mA / cm 2The deposition time varies within the range of 15min-12min, as follows:
[0068] a. The current density when depositing the first pure nickel layer is 40mA / cm 2 , the deposition time is 15min;
[0069] b. The current density when depositing the second pure nickel layer is 40mA / cm 2 , the deposition time is 15min;
[0070] c. The current density when depositing the third pure nickel layer is 50mA / cm 2 , the deposition time is 15min;
[0071] d. When depositing the fourth pure nickel layer, the current density is 60mA / cm 2 , the deposition time is 13min;
[0072] e. The current density when depositing the fifth pure nickel layer is 80mA / cm 2 , the deposition time is 12min;
[0073] At the same time, adjust the bath temperature:
[0074] a. The plating temperature is 75°C when depositing the first pure nickel layer;
[0075] b. The plating solution temperature is 65°C when depositing the second pure nickel layer;
[0076] c. The plating temperature is 50°C when depositing the third pure nickel layer;
[0077] d. When depositing the fourth pure nickel layer, the bath temperature is 50°C;
[0078] e. The bath temperature is 45°C when depositing the fifth pure nickel layer;
[0079] The temperature adjustment in the stages a, b, c, d and e is all uniform.
[0080] The nickel / nickel-molybdenum gradient lamellar structure alloy sample II was prepared in this embodiment. Figure 2 As shown in (a), the coating quality of sample I is good, the interface is well bonded, and there are no obvious microcracks.
[0081] The grain size distribution of the nickel layer in the nickel / nickel-molybdenum gradient lamellar structure alloy sample Ⅱ is shown in Figure 2. Figure 2As shown in (b)-(f), the grain size in the direction of the long axis of the grain shows a gradually decreasing trend, with the specific changes being 3851nm→2259nm→633nm→480nm→54nm; the grain size in the direction of the short axis of the grain shows an overall gradually decreasing trend, with the specific changes being 590nm→548nm→254nm→371nm→30nm.
[0082] The cross-sectional hardness distribution of Ni / NiMo gradient lamellar structure alloy specimen II is shown in Figure 2. Figure 2 As shown in (g), the hardness of the pure nickel layer gradually increases from 322HV to 587HV, and the specific changes are 322HV→405HV→483HV→542HV→587HV; the hardness of the nickel-molybdenum alloy layer is maintained at 638HV. Figure 3 As shown in the figure, the wear rates under loads of 10N, 20N, 40N, 60N, and 80N are 1.91×10 -6 mm 3 / N·m, 2.97×10 -6 mm 3 / N·m, 5.45×10 -6 mm 3 / N·m,6.52×10 -6 mm 3 / N·m,8.97× -6 mm 3 / N·m, compared with coarse-grained nickel (grain size is about 30μm), its wear rate is reduced by 59%, 78%, 76%, 84% and 86% under loads of 10N, 20N, 40N, 60N and 80N, respectively.
[0083] Nickel / nickel-molybdenum gradient lamellar structure alloy specimens I and II refer to Figure 3 As shown in the figure, it can be seen that the wear rate of nickel / nickel-molybdenum gradient lamellar structure alloy samples I and II under a load of 10-80N is significantly lower than the wear rate of coarse-grained nickel. This shows that the nickel-based gradient lamellar structure can effectively improve the wear resistance of nickel-based alloys.
Claims
1. A method for preparing a nickel-nickel-molybdenum gradient lamellar structure alloy, characterized in that: Electrochemical deposition is adopted, with nickel as the consumable anode, and pure nickel layer and nickel-molybdenum alloy layer are alternately deposited under the action of direct current; wherein the pure nickel layer from the inside to the outside has a grain size gradient of micron coarse crystal-ultrafine crystal-nanocrystalline transition by controlling the composition of the plating solution, the current density and the plating solution temperature, and the nickel-molybdenum alloy layer has an ultrafine nanocrystalline structure.
2. The method according to claim 1, characterized in that: The specific steps include: Step (1): Substrate pretreatment: surface grinding, polishing and degreasing are performed in sequence, followed by water washing, acid washing activation and water washing; Step (2): immersing the treated substrate in a pure nickel electroplating solution and preparing a pure nickel layer by direct current electrodeposition; Step (3): taking out the sample obtained in step (2), washing it with water, acid washing it to activate the pure nickel layer, washing it with water, and then immersing it in a nickel-molybdenum alloy electroplating solution to prepare a nickel-molybdenum alloy coating by direct current electrodeposition; Step (4): Take out the sample obtained in step (3), wash it with water, pickle it to activate the nickel-molybdenum alloy layer, and wash it with water, then periodically repeat steps (2) and (3) alternately, and when repeating step (2), adjust the plating solution temperature and current density in real time to achieve the construction of the grain size gradient structure, and finally prepare a nickel / nickel-molybdenum gradient layer structure alloy with M layers of pure nickel layer and M layers of nickel-molybdenum alloy layer respectively and a total number of 2M layers, where M is a positive integer.
3. The method according to claim 2, characterized in that The cathode for electrochemical deposition is titanium, copper, copper alloys, steel or nickel and nickel alloys.
4. The method according to claim 3, characterized in that The pure nickel electroplating solution in step (2) comprises nickel sulfate hexahydrate with a concentration of 100-300 g / L, nickel chloride hexahydrate with a concentration of 30-45 g / L, boric acid with a concentration of 20-40 g / L, and sodium dodecyl sulfate with a concentration of 0.1-0.5 g / L; the pH of the pure nickel electroplating solution is adjusted to 4.5±0.
5.
5. The method according to claim 4, characterized in that The nickel-molybdenum alloy electroplating solution in step (3) comprises nickel sulfate hexahydrate with a concentration of 60-80 g / L, sodium citrate dihydrate with a concentration of 80-100 g / L, sodium molybdate dihydrate with a concentration of 1-3 g / L, vinyl acetate with a concentration of 0.1-0.5 g / L, sodium saccharin with a concentration of 0-5 g / L, and sodium dodecyl sulfate with a concentration of 0.1-0.5 g / L; the pH of the nickel-molybdenum alloy electroplating solution is adjusted to 9±0.
5.
6. The method according to claim 5, characterized in that "By controlling the composition, current density and temperature of the plating solution, the pure nickel layer from the inside to the outside has a grain size gradient of micron coarse crystals, ultrafine crystals and nanocrystals" is specifically: The deposition current density of pure nickel layer increases from 40±1mA / cm 2 Gradually increase to 80±2mA / cm 2 , specifically: When depositing the first pure nickel layer, the current density is 40±1mA / cm 2 ; When depositing the Mth pure nickel layer, the current density is 80±2mA / cm 2 ; When depositing the Nth pure nickel layer, where 1≤N≤M and is a positive integer, the current density is The deposition temperature of the pure nickel layer gradually decreases from 75±2℃ to 45±1℃ as the number of layers increases, specifically: When depositing the first pure nickel layer, the bath temperature is 75±2°C; When depositing the final layer, i.e., the M layer of pure nickel, the bath temperature is 45±1°C; When depositing the Nth pure nickel layer, where 1≤N≤M and is a positive integer, the temperature is 7. The method according to claim 6, characterized in that When depositing the nickel-molybdenum alloy layer, the deposition current density of the nickel-molybdenum alloy layer remains constant as the number of layers increases, which is 30±1mA / cm 2 ; The temperature of the nickel-molybdenum alloy electroplating solution remained constant at 35±1°C as the number of layers increased.
8. The method according to claim 7, characterized in that Nickel tungsten, nickel cobalt, nickel iron, nickel phosphorus or nickel boron are used instead of nickel molybdenum.
9. A nickel-nickel-molybdenum gradient lamellar structure alloy, characterized in that: The method described in any one of claims 1 to 7 is used for preparation; the grain size of the pure nickel layer of the nickel-nickel-molybdenum gradient lamellar structure alloy is gradually refined from 2-5μm to 20-30nm; the grain size of the nickel-molybdenum alloy layer is 10±2nm; the thickness ratio between the pure nickel layer and the nickel-molybdenum alloy layer is 5:1 to 50:
1.
10. Use of the nickel-nickel-molybdenum gradient lamellar structure alloy according to claim 9, characterized in that: Used for the inner bore of a gun barrel.